Artemisinin inhibits TLR4 signaling by targeting co‐receptor MD2 in microglial BV‐2 cells and prevents lipopolysaccharide‐induced blood–brain barrier leakage in mice. Issue 3 (2nd February 2021) - Zhang, Tianshu; Zhang, Xiaozheng; Lin, Cong; Wu, Siru; Wang, Fanfan; Wang, Hongshuang; Wang, Yibo; Peng, Yinghua; Hutchinson, Mark R.; Li, Hongyuan; Wang, Xiaohui
Abstract: Artemisinin and its derivatives have been the frontline drugs for treating malaria. In addition to the antiparasitic effect, accumulating evidence shows that artemisinins can alleviate neuroinflammatory responses in the central nervous system (CNS). However, the precise mechanisms underlying their anti‐neuroinflammatory effects are unclear. Herein we attempted to delineate the molecule target of artemisinin in microglia. In vitro protein intrinsic fluorescence titrations and saturation transfer difference (STD)‐NMR showed the direct binding of artemisinin to Toll‐like receptor TLR4 co‐receptor MD2. Cellular thermal shift assay (CETSA) showed that artemisinin binding increased MD2 stability, which implies that artemisinin directly binds to MD2 in the cellular context. Artemisinin bound MD2 showed much less collapse during the molecular dynamic simulations, which supports the increased stability of MD2 upon artemisinin binding. Flow cytometry analysis showed artemisinin inhibited LPS‐induced TLR4 dimerization and endocytosis in microglial BV‐2 cells. Therefore, artemisinin was found to inhibit the TLR4‐JNK signaling axis and block LPS‐induced pro‐inflammatory factors nitric oxide, IL‐1β and TNF‐α in BV‐2 cells. Furthermore, artemisinin restored LPS‐induced decrease of junction proteins ZO‐1, Occludin and Claudin‐5 in primary brain microvessel endothelial cells, and attenuated LPS‐induced blood–brain barrier disruption in mice as assessed by Evans blue. In all, this study unambiguously adds MD2 as a direct binding target of artemisinin in its anti‐neuroinflammatory function. The results also suggest that artemisinin could be repurposed as a potential therapeutic intervention for inflammatory CNS diseases. Abstract : Toll‐like receptor TLR4 co‐receptor MD2 is a novel direct binding target of artemisinin in its anti‐neuroinflammatory function. Artemisinin binds to MD2, which stabilizes the MD2 conformation and inhibits the dimerization and endocytosis of TLR4. This results in blockade of TLR4‐JNK signaling axis and the LPS induced production of proinflammatory mediators. Furthermore, artemisinin attenuates the LPS‐induced BBB disruption. These results suggest that artemisinin could be repurposed as a potential therapeutic intervention for inflammatory CNS diseases.